MATEC Web of Conferences - Rybalka specialist in the field of Informatics and computer engineering associate Professor of Tomsk Polytechnic University, candidate of technical Sciences; Yuzhakov specialist in the field of non-destructive testing Associate Scientist of Tomsk Polytechnic University; Ivanov specialist in the field of nondestructive testing engineer at Tomsk Polytechnic University; Nguyen Dang Quang specialist in the field of non-destructive testing engineer of Tomsk Polytechnic University; Kodermjatov; Guo Wenjia; Maksimov; Zimin (2018)
The problems of designing the system for automatic analysis of cardiograms are considered. The structure of the system for recording and storing electrocardiograms was formed. The procedures that make up the complex of automatic analysis are listed.